Atividades, conteúdos e procedimentos no laboratório de informática em escolas públicas - Campos, Nilson Sampaio (2013)
Inserted in the broad theme of the integration of Information and Communication Technologies (ICT) to education this research, empirical analyzes the activities, contents and procedures of classroom computer lab education (LIE) in two public schools in the city of Taubaté-SP. The research aims to examine the functioning and uses data to LIE, by observing the structural conditions of schools and pedagogical conditions for the work of teachers and trainees. The discussion on the observation data is linked to the theoretical contributions, noting that the authors study the integration of ICT in schools and educational policies for this purpose. Authors of the critical theory of society, as Adorno and Marcuse, allowed to consider the phenomenon of ICT within the industrial technology-based society; Marin and Lawn, through discussions on the training of teachers and social representation of the teaching profession, supported the analysis about actions in teaching LIE. The results support the view that the spread of ICT in the Brazilian public education system is stimulated by a tendency which permeates and sociocultural impacts teaching practices. The pressure experienced by schools and teachers shapes and limits the pedagogical practice. However, the main brand is precarious: the lack of structure of the school and also the LIE, beyond the limits imposed by technology, causes the use of ICT and instrumental lessons inarticulate and significant